Multiple myeloma presenting with coexisting severe marrow hypoplasia - Medhi K; Kalita Dipti; Chopra Anita; Anand Mona; Raina Vinod; Kumar Rajive (Wolters Kluwer Medknow Publications, 2008)
A 68-year-old man was referred to us with clinical and bone marrow (BM) features compatible with aplastic anemia. The correct diagnosis, hypoplasia of the BM coexisting with multiple myeloma, became apparent after noting rouleaux in the peripheral blood (PB) and approximately 50% plasma cells in the touch imprint of one of the two BM biopsies done. As standard therapy was precluded, the patient was put on dexamethasone but died within 4 days. This first case of the coexistence of untreated myeloma with aplastic BM shows that even apparently straightforward hypoplasia seen on the BM biopsy should be interpreted in conjunction with the PB smear and the BM touch imprint findings. Among other things, the BM biopsy and imprint should be repeated if the PB has findings such as rouleaux that do not fit with straightforward aplastic anemia. The combination of myeloma and BM aplasia precludes standard therapy and is rapidly fatal.